(x*3)-(48*72)=3456

Simple and best practice solution for (x*3)-(48*72)=3456 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x*3)-(48*72)=3456 equation:


Simplifying
(x * 3) + -1(48 * 72) = 3456

Reorder the terms for easier multiplication:
(3x) + -1(48 * 72) = 3456

Multiply 48 * 72
(3x) + -1(3456) = 3456

Multiply -1 * 3456
(3x) + -3456 = 3456

Reorder the terms:
-3456 + (3x) = 3456

Solving
-3456 + (3x) = 3456

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3456' to each side of the equation.
-3456 + 3456 + (3x) = 3456 + 3456

Combine like terms: -3456 + 3456 = 0
0 + (3x) = 3456 + 3456
(3x) = 3456 + 3456

Combine like terms: 3456 + 3456 = 6912
(3x) = 6912

Divide each side by '3'.
x = 2304

Simplifying
x = 2304

See similar equations:

| Solvem-4n=8form | | 5/12=x/108 | | 3v+14=59 | | -4x^2-10=-2(5-x^2) | | (x*3)-(48*y)=3456 | | y=5/4*5/4+10 | | 9y^2+3y=0 | | x/8+15=32 | | x/8+15 | | .50n=-101 | | y/3=4x-3 | | 4x+3y=-y | | 43.75=7w | | 2v=25.6 | | 0.4+3(1.2t+0.9)=21.1 | | 8=z+9 | | -5-5a=5(1+a) | | y=-4/9*4+4 | | y=-4/9(-4/9)+4 | | 3x=5(3x-8) | | 5x+3y=80 | | 3x+7(2x-8)=15 | | -27=12w+27 | | 5n^2-15n=0 | | 2x+x+16=32 | | -21=n*3+2 | | 32=30-k/16 | | 5n*2-15n=0 | | 9x-3=15x+12 | | 4y+3x=5x | | -5=-9+w | | -5=-9w |

Equations solver categories